Sosialisasi Penanganan Penyakit dan Demplot Pembuatan Herbal Sederhana pada Ayam Kampung di Desa Liang Kecamatan Salahutu Saat Musim Penghujan - Wiesje Martha Horhoruw; Arnold Ismael Kewilaa (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this activity is to socialize disease management and demonstration plots for making simple herbal remedies for native chickens in Liang Village, Salahutu District during the rainy season. This activity was carried out in Liang Village, Salahutu District, which took place in September 2025. The target of this activity is native chicken farmers in Liang Village, Salahutu District. The implementation of this PKM activity includes 3 stages, namely: preparation, implementation and monitoring evaluation. The results obtained from the PKM activity are the implementation of socialization activities and demonstration plots for making simple herbal remedies for farmers in Liang Village, Salahutu District, Central Maluku Regency. Socialization related to types of diseases, treatment and prevention of diseases in native chickens. The conclusions that can be conveyed are as follows: increased knowledge about the introduction of native chicken diseases and their prevention, the creation of motivation for business development because they have the right knowledge about the advantages of raising native chickens, increased knowledge and skills about making and administering simple herbal remedies to native chickens, increased knowledge and desire to try native chicken farming as a source of nutritious food and can increase family income, and low mortality rates of native chickens in the rainy season.